The Impact of Serial Remote Ischemic Conditioning on Dynamic Cerebral Autoregulation and Brain Injury Related Biomarkers - Qu, Yang; Zhang, Peng; He, Qian-Yan; Sun, Ying-Ying; Wang, Mei-Qi; Liu, Jia; Zhang, Pan-Deng; Yang, Yi; Guo, Zhen-Ni (Frontiers in Physiology, 2022)
Objective: Recent studies have demonstrated the positive roles of remote ischemic conditioning (RIC) in patients with cerebrovascular diseases; however, the mechanisms remain unclear. This study aimed to explore the effect of serial RIC on dynamic cerebral autoregulation (dCA) and serum biomarkers associated with brain injury, both of which are related to the prognosis of cerebrovascular disease. Methods: This was a self-controlled interventional study in healthy adults. The RIC was conducted twice a day for 7 consecutive days (d1–d7) and comprised 4×5-min single arm cuff inflation/deflation cycles at 200 mmHg. All participants underwent assessments of dCA ten times, including baseline, d1, d2, d4, d7, d8, d10, d14, d21, and d35 of the study. Blood samples were collected four times (baseline, d1, d7, and d8) immediately after dCA measurements. The transfer function parameters (phase difference [PD] and gain) were used to quantify dCA. Four serum biomarkers associated with brain injury, ubiquitin C-terminal hydrolase-L1, neuron-specific enolase, glial fibrillary acidic protein and S100β were tested. Results: Twenty-two healthy adult volunteers (mean age 25.73±1.78 years, 3 men [13.6%], all Asian) were enrolled in this study. Bilateral PD values were significantly higher since four times of RIC were completed (d2) compared with PD values at baseline (left: 53.31±10.53 vs. 45.87±13.02 degree, p=0.015; right: 54.90±10.46 vs. 45.96±10.77 degree, p=0.005). After completing 7 days of RIC, the significant increase in dCA was sustained for at least 28 days (d35, left: 53.11±14.51 degree, P=.038; right: 56.95±14.57 degree, p<0.001). No difference was found in terms of different serum biomarkers related to brain injury before and after RIC. Conclusions: The elevation in dCA was detected immediately after four repeated times of RIC, and 7-day consecutive RIC induced a sustained increase in dCA for at least 28 days and did not affect blood biomarkers of brain injury in healthy adults. These results will help us to formulate detailed strategies for the safe and effective application of RIC in patients with cerebrovascular disease.